Literary Ethnography in Lyrical Text (Poetic Ethnographism by Larissa Andersen) - Anna A. Zabiyako; Olga E. Tsmykal (Гуманитарный вектор, 2021)
The relevance of the study determines the interest of modern literary criticism in various forms of artistic understanding of ethnographic realities by Russian writers in Manchuria in the first half of the 20th century (literary ethnography). The novelty of the research lies in the study of the lyrical experiments of literary ethnography. The research problem is to determine the specificity of the lyrical method of ethnographic reflection and the creation of an image of artistic perception. The research methodology is based on the structural and semantic analysis выскаof prose texts by Larissa Andersen, addressed to ethnographic material. The authors explore the methods of creating her artistic images of perception of China, Korea, and Japan through the analysis of narrative strategies, the system of image-concepts, and archetypal images of a foreign culture. Research methods: historical-literary, structural-semantic, method of mythological reconstructions, comparative analysis of the translation with the original. The authors state that the literary ethnography of the Far East in various genre and stylistic forms is developing in the literature of the Far Eastern emigration. The most convincing experiences of artistic ethnography, scientific and artistic beginnings are balanced, presented in the narratives of scientific writers N. Baikov and P. Shkurkin, and later genre modifications of M. Shcherbakov, V. Mart, B. Yulsky, focused on research and book experience. Lyrical reflection of ethnographic material has its own specifics. The authors compared the experiences of creating ethnographic lyrics and prose by Larissa Andersen and came to the following conclusions: despite the lack of well-founded scientific knowledge, in her ethnographic essays, on the one hand, her individual ability to comprehend the essence of the observed phenomenon and capture the artistic image of the perception of another culture in capacious detail-concept (mythologeme, characteristic, ethno-stereotype, meta-image), on the other hand, there is an interest in Chinese literary sources and ethnographic texts of predecessors (S. Alymova and others). A characteristic technique for creating an artistic image of perception in essays is the form of personal “narration”, bringing the point of view of the perceiving consciousness of the author and the reader closer together.